FUNGSI DAN MAKNA UPACARA NGANTENAG KARANG DI DESA ADAT SUBAGAN KARANGASEM - I Wayan Lali Yogantara; I Wayan Darna (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
In Desa Adat Subagan Karangasem, the Ngantenang Karang Ceremony is often held, a Hindu ritual that is associated with the activity of combining two house yards. The Ngantenang Karang Ceremony is manifested in the religious aspect, to declare the presence of Ida Sang Hyang Widhi Wasa and the Sang Ibu Pertiwi that a merger of two plots of land will be accompanied by an upakara (banten) which will be presented before him in order to invoke the blessing and safety and psychological aspects, namely to merge obtain a sense of comfort; latent functions in the socio-cultural aspects of realizing togetherness, and preservation of culture, educative aspects namely the application of ethical education to realize harmony; as well as economic functions, namely to save costs both in terms of environmental cleanliness of the yard and religious ceremonies. Constructive meaning with its efforts as a symbol of presenting Ida Sang Hyang Widhi Wasa, welcomed, served a dish and then requested to be pleased to provide clean or purity of the bhuwana agung and bhuwana alit, safety and success as well as fusion or unification; evaluative means that the application of positive norms in accordance with applicable and moral standards for the sake of the realization of peace, harmony and karahayuan; cognitive meaning that is building and maintaining the cleanliness and sanctity of the new yard for the sake of creating harmony between the parties both the owner of the yard with Ida Sang Hyang Widhi Wasa, between the family members of the owner of the house and between family members of the owner of the house and the natural environment; and expressive meaning that is able to realize the owner of the yard feels happy, peaceful, and happy.